Slag Hauler User Interface Design : Using human-centred design to create a user interface for heavy machinery - Rondahl, Robert; Larsson, Filip (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2017)
Within the field of heavy machinery, the driver environment and its user interface (UI) has not always been a high priority during product development. This is about to change since the user experience, especially of the driver, becomes more of a selling point. Kiruna Utility Vehicles (Kiruna UV), who manufactures slag haulers for the steel industry, has developed a new driver cabin to meet these future demands. The development has been conducted in collaboration with students at Luleå University of Technology. This master thesis aims to create a basis for the digital user interface of the Kiruna UV SH60 slag hauler. The needs of the users are very important in order to ensure a good user experience. This is why a human-centred design process was chosen for this project. Extensive research has been conducted with the drivers, mechanics, managers and manufacturer of the SH60 slag hauler. Research was conducted through field studies, where interviews, observations and eye tracking were used as the main tools.The slag hauler driver operates the vehicle in two positions, where the need for information differs. When the slag hauler is driven the driver is facing forward and in this position the slag hauler is similar to any other heavy machinery. The UI needs to display for example speed, gear and RPM. When loading or emptying slag pots, the driver turns around to manoeuvre the tipping system. In this position, information about the lockings, support legs and tipping system is the most important.Through brainstorming sessions and ideation workshops with the manufacturer and participants without connection to the slag hauler, ideas on how different types of information can be shown were generated. Ideas regarding layout of the UI were also produced. These ideas were then mapped onto four different concepts that were developed through several iterations. These were then evaluated through a survey study, a usability test and feedback sessions with slag hauler drivers, mechanics and the manufacturer.A final concept was ...